2019
DOI: 10.1007/978-3-030-24299-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Wind Balance in Daily Electricity Markets: A Case-Study

Abstract: The European Union has been one of the major drivers of the development of renewable energy. In Portugal, renewable generation is subject to specific licensing requirements and benefits from a feedin-tariff. This paper pays special attention to wind and hydroelectric technologies. Typically, wind farms produce more energy during the night (off-peak periods), when the demand is lower, contributing to a reduction of the market price. Hydroelectric power plants use off-peak periods to pump water, and produce ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In our previous work [22], we performed a preliminary analysis of the hydro-wind balance in the Portuguese electric system. Specifically, we conducted a simulation-based study and confirmed the (well-known) conclusions that HPPs consider the hours with low market prices (normally involving a high wind power level and/or a low demand) to pump, and the hours with high market prices (normally peak hours with a high demand) to produce energy.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [22], we performed a preliminary analysis of the hydro-wind balance in the Portuguese electric system. Specifically, we conducted a simulation-based study and confirmed the (well-known) conclusions that HPPs consider the hours with low market prices (normally involving a high wind power level and/or a low demand) to pump, and the hours with high market prices (normally peak hours with a high demand) to produce energy.…”
Section: Introductionmentioning
confidence: 99%